Synthesis and biological evaluation of indane-based fluorescent probes for detection of amyloid-β aggregates in Alzheimer’s disease - Lee, Hyunseung; Kim, Yihoon; Aziz, Hira; Kang, Dong Min; Lee, Jaewoon; Lee, Sujin; Jung, Sunhwa; Hyeon, Suyeon; Choo, Hyunah; Nam, Ghilsoo; Kim, Yun Kyung; Lim, Sung su; et al. (Pergamon Press Ltd., 2023)
In this article, the development of fluorescent imaging probes for the detection of Alzheimer's disease (AD)-associated protein aggregates is described. Indane derivatives with a donor-π-acceptor (D-π-A) structure were designed and synthesized. The probes were evaluated for their ability to bind to β-amyloid (Aβ) protein aggregates, which are a key pathological hallmark of AD. The results showed that several probes exhibited significant changes in fluorescence intensity at wavelengths greater than 600 nm when they were bound to Aβ aggregates compared to the Aβ monomeric form. Among the tested probes, four D-π-A type indane derivatives showed promising binding selectivity to Aβ aggregates over non-specific proteins such as bovine serum albumin (BSA). The molecular docking study showed that our compounds were appropriately located along the Aβ fibril axis through the hydrophobic tunnel structure. Further analysis revealed that the most active compound having dimethylaminopyridyl group as an election donor and dicyano group as an electron acceptor could effectively stain Aβ plaques in brain tissue samples from AD transgenic mice. These findings suggest that our indane-based compounds have the potential to serve as fluorescent probes for the detection and monitoring of Aβ aggregation in AD.